Evaluation of Loss Resources during Sugarcane Production Process and Provide Solutions to Reduce Waste - H Zaki Dizaji (Ferdowsi University of Mashhad, 2018)
Introduction No use of advanced mechanization and weakness in post harvesting technology are the main reasons of agricultural losses. Some of these wastes (agricultural losses) are related to crop growing conditions in field and the remaining to processing of sugar in mill. The most useful priority setting methods for agricultural projects are the Analytic Hierarchy Process (AHP). So, this study presents an introduction of application manner of the AHP as a mostly common method of setting agricultural projects priorities. The purpose of this work is studying the sugarcane loss during production process using AHP in Khuzestan province. Materials and Methods The resources of sugarcane waste have been defined based on expert’s opinions. A questionnaire and personal interviews have formed the basis of this research. The study was applied to a panel of qualified informants made up of thirty-two experts. Those interviewed were distributed in Sugarcane Development and By-products Company in 2015-2016. Then, with using the analytical hierarchy process, a questionnaire was designed for defining the weight and importance of parameters effecting on sugarcane waste. For this method of evaluation, three main criteria considered, were yield criteria, cost criteria and income criteria. Criteria and prioritizing of them was done by questionnaire and interview with sophisticated experts. This technique determined and ranked the importance of sugarcane waste resources based on attributing relative weights to factors with respect to comments provided in the questionnaires. Analytical Hierarchy Process was done by using of software (Expert choice) and the inconsistency rate on expert judgments was investigated. Results and Discussion How to use agricultural implements and machinery during planting and harvesting of sugarcane, can increase or decrease the volume of waste. In planting period, the losses mainly consists of loss of setts during cutting them by machine, injury the setts by biological and physical agents, loss of growth in sett field, unsuitable sett covering and replanting the gaps. During cultivation period the losses include late in field harvesting and so late in regrows the cane, unsuitable ratooning and use of cultivator, varying the size of the furrows and ricks in around the field and destroyed the stubbles during rationing. In harvesting the losses easily seen and mainly associated by efficiency of harvester machines. Billets loss of the fleet in the transmission roads toward mill and late in harvest the burnet cane and then transport to mill are main sources of quantities and qualities of losses. The Expert Choice software performed well in conjunction with the panel of experts for choosing the criteria and assigning weights under the AHP methodology. According to the results, effective parameters on sugarcane waste consist of caused by harvesting, transportation, industry, planting, preserve operations, ratooning and land preparation. Weight of effective criteria (yield, cost and income) on losses of sugarcane obtained from paired comparison in the experts’ view which has been calculated with Expert choice software. The result of this survey by AHP techniques showed that yield criteria had the most and income criteria had the least importance for expert in sugarcane production. In this stage of research, alternatives of paired comparison relative to criteria was separately formed and information of questionnaire which relates to paired comparison of criteria was obtained. Between effective parameters on losses of sugarcane, harvesting with 0.243 weighted average was the most effective factor and transportation with 0.187 weighted average, industry with 0.179 weighted average, planting with 0.156 weighted average, preserve operations with 0.109 weighted average, ratooning with 0.071 weighted average, and land preparation with 0.055 weighted average was later, respectively (Inconsistence Rate =0.04). The results are examined by monitoring sensitivity analysis while changing the criteria priorities. Since different judgments are made on comparison of criteria, we use sensitivity analysis in order to provide stability and consistence of analysis. With increasing or decreasing of the criteria, we will conclude that ratio of other indices will not change. Conclusions This paper looks at AHP as a tool used in Sugarcane Agro-Industries to help in decision making. Results show that criteria studied in this research can help prioritizing of loss resources during sugarcane production process. According to the results, effective parameters on sugarcane waste consist of caused by harvesting, transportation, industry, planting, preserve operations, ratooning and land preparation.